Differences in Food Craving in Individuals With Obesity With and Without Binge Eating Disorder - Reents, Janina; Pedersen, Anya (Frontiers in Psychology, 2021)
Overeating behavior is supposedly a major contributing factor to weight gain and obesity. Binge eating disorder (BED) with reoccurring episodes of excessive overeating is strongly associated with obesity. Learning models of overeating behavior and BED assume that mere confrontation with food leads to a conditioned response that is experienced as food craving. Accordingly, individuals with obesity and BED were shown to have high trait food cravings. To date, little is known about differences in state food cravings and cue reactivity at the sight of palatable food in individuals with obesity and BED compared to individuals with obesity without BED. Therefore, the aim of our study was to examine differences in cue-induced, state and trait food cravings in people with obesity with and without BED. We found that all aspects of food cravings were more prevalent in individuals with obesity and BED than in individuals without BED. By implementing a food cue reactivity paradigm, our results show that individuals with obesity with BED have more cue-induced cravings than individuals with obesity without BED. Moreover, these cue-induced cravings in individuals with obesity and BED were highest for high-fat and high-sugar foods as opposed to low-calorie foods. Thus, our results emphasize the role of increased cue reactivity and craving at the sight of palatable foods in individuals with obesity and BED. Hence, our findings support etiological models of conditioned binge eating and are in line with interventions targeting cue reactivity in BED.